2014
DOI: 10.1136/bcr-2014-205584
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus and granular dystrophy

Abstract: SUMMARYConcurrent bilateral keratoconus and granular dystrophy is reported in a 32-year-old patient with decreased vision. Initially contact lenses were attempted unsuccessfully to treat the conditions. There are a handful of other reports of these combined pathologies in the literature, and the likelihood of a chance cause or possible genetic linkage between the conditions is discussed. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…A lower SSI in GCD compared to normal corneas confirmed these changes in involved corneas. In addition, the present findings are in line with other studies that simultaneously reported the association of GCD with keratoconus [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…A lower SSI in GCD compared to normal corneas confirmed these changes in involved corneas. In addition, the present findings are in line with other studies that simultaneously reported the association of GCD with keratoconus [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although KTCN is sometimes referred to as a corneal dystrophy, it is not included in International Classification of Corneal Dystrophies (IC3D) (Weiss et al 2008 ) and should be distinguished from this group of corneal diseases. However, co-occurrence of KTCN with many types of corneal dystrophies, including Avellino and Fuchs dystrophies (Igarashi et al 2003 ; Salouti et al 2010 ; Wilson et al 2014 ), may indicate that common molecular mechanisms in the pathogenesis of these disorders are involved.…”
Section: Introductionmentioning
confidence: 99%
“…GCD with keratoconus is rarely reported. [ 1 2 3 4 ] Although no evidence-based analysis has linked this association, many theories have been proposed, including abnormal synthetic activity of keratocytes and degeneration of defective basal epithelial cells, speculated to occur in both. [ 2 ] While GCD is clinically obvious, this case emphasizes the need to identify associated factors in effective planning and management.…”
mentioning
confidence: 99%